2013
DOI: 10.1002/art.37976
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: High‐Throughput Sequencing of IL23R Reveals a Low‐Frequency, Nonsynonymous Single‐Nucleotide Polymorphism That Is Associated With Ankylosing Spondylitis in a Han Chinese Population

Abstract: Objective. Ankylosing spondylitis (AS) is a highly heritable common inflammatory arthritis that targets the spine and sacroiliac joints of the pelvis, causing pain and stiffness and leading eventually to joint fusion. Although previous studies have shown a strong association of IL23R with AS in white Europeans, similar studies in East Asian populations have shown no association with common variants of IL23R, suggesting either that IL23R variants have no role or that rare genetic variants contribute. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Rather, a different variant (rs76418789, G149R) is AS-associated in east Asians. 55 This variant shows weak association in European descent populations too but that effect is difficult to see because of the strength of association of other variants at this locus, notably rs11209026 (R381Q).…”
Section: Non-mhc Genetic Associationsmentioning
confidence: 99%
“…Rather, a different variant (rs76418789, G149R) is AS-associated in east Asians. 55 This variant shows weak association in European descent populations too but that effect is difficult to see because of the strength of association of other variants at this locus, notably rs11209026 (R381Q).…”
Section: Non-mhc Genetic Associationsmentioning
confidence: 99%
“…These two SNPs are in moderate LD (r 2 = 0.63, Table 2) and may detect the same functional variant in both populations. Interestingly, low frequency missense variants of the IL23R (p.Arg381Gln in the Turkish population and p.Gly149Arg in the Japanese population) that reduce its ability to respond to IL-23 stimulation have been associated with protection from BD [69], as well as from ankylosing spondylitis (AS) [70, 71], psoriasis [72, 73], Crohn’s disease [74], ulcerative colitis [75] and inflammatory bowel disease (IBD) [76, 77], suggesting that the intergenic disease-associated common non-coding variants might be associated with increased expression of IL23R compared with the disease-protective minor alleles.…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…While the association was confirmed in subsequent studies of individuals of European descent (13), the IL23R association was not found in Korean (48) or Chinese populations (41,49). However, a recent study identified several rare IL23R variants in a Chinese population, including a non-synonymous SNP predicted to reduce function that is associated with protection from AS (50). …”
Section: The Il-23/il-17 Axismentioning
confidence: 99%